Pengembangan Formulasi Sirup Berbahan Baku Kulit dan Buah Nanas - Shanti Fitriani; Evi Sribudiani (Universitas Riau, 2009)
Pineapple fruit flesh has higher economic value than the pineapple skin. Therefore the use of pineapple skin in making products such as syrup will increase its economic value. This study aimed to determine pH, total dissolved solid and panelist aceptance of the syrup from pineapple fruit flesh and skin. This study consisted of 5 combinations as follow: K0 (100% pineapple flesh), K1 (25% pineapple skin + 75% pineapple flesh), K2 (50% pineapple skin+50% pineapple flesh), K3 (75% pineapple skin + 25% pineapple skin), K4 (100 pineapple skin). The experiment was conducted in completely randomized design with 3 replications. Parameter observed were pH, total the pH value of the syrup was not significantly different between all treatment, while total dissolved solid of syrup from pineapple flesh and skim produced was significantly differen. Syrup from up to 75% pineapple skin was still acceptable by the panelists for taste, colour, aroma and overall acceptance.